The The Study of Local Identity for Brand Design for Image-Building towards Consumer Acknowledgement : A Case Study of Bang Nang Lee Subdistrict, Amphawa District, Samut Songkhram Province - Nudang, Sopa; Binder, Wilailak; Sompoangeon, Saneh; Busamsai, Vorachat (Parichart Journal, 2024)
The objectives of this research paper were to: 1) study and analyze Bang Nang Lee Sub-district’s identity, 2) implement Bang Nang Lee’s identity in the brand design, and 3) analyze the perceptions of Bang Nang Lee’s brand products. A Mixed-method research was utilized in the study. The samples included 306 tourists and 31 main informants on research. The areas under study were purposefully chosen. The data collection tools included observations, interviews, group discussions, assessment forms, and questionnaires. The quantitative data were analyzed using descriptive statistics, including frequency and percentage. The qualitative data were analyzed using content analysis. The results of the research revealed as follows. 1) The local identity of Bang Nang Lee consisted of physical identities that were physical characteristics, which was considered to be Bang Nang Lee’s strength. Also, the intangible identity involved community wisdom, beliefs, faith, social activities, traditions, and culture that developed into local people’s attachment and mutual memory. 2) The transference of Bang Nang Lee sub-district identity to develop a brand that was applied in brand design gave artistic elements symbols from both concrete and abstract forms identity, which were color themes, shape groups, texture groups, and text groups. Then, they were used to design a brand named "Nang Lee." These were evaluated and found that they were appropriate and the appropriateness was rated at a high level. 3) The analyzed data on the consumer perceptions towards the brand images was also found at a high level.